STABILITY ANALYSIS OF DRUG ABUSE TRANSMISSION DYNAMICS - Zakiyyah, Abqorry; Bahri, Susila (Departemen Matematika dan Sains Data FMIPA Universitas Andalas Padang, 2025)
This research introduced a nonlinear deterministic model known as SLARS (Susceptible, Light Users, Addicted, and Reformed Users) along with a stability analysis to investigate the dynamics of drug abuse transmission. The basic reproduction number (R0) was calculated using the next-generation matrix method. Following this, the study examined the local stability of both the drug abuse-free and endemic equilibrium points. The findings indicated that when R0 is below 1, the drug abuse-free equilibrium point is locally stable. In contrast, when R0 is greater than 1, the endemic equilibrium point shows local stability. Additionally, simulation results supported the analytical conclusions of the study.